Usuário da informação um velho desconhecido: usuários da informação em diferentes profissões da informação - Eliane Cristina de Freitas Rocha (2013)
This doctoral dissertation investigates how information users have been approached in the professional practice of librarians and IT analysts, comparing the theoretical and methodological approaches of information users by both professional categories, aiming to contribute to the user studies field of Information Science. In order to reach this goal 17 librarians and 16 system analysts were interviewed from organizations of different sizes and fields, including innovation technology centres. The main finding of this doctoral dissertation are as follows: the IT analysts and the librarians deal with the information users under a functionalist approach: the user is anyone who uses any informational resource to accomplish a task in their working roles or library roles (student, teacher, reader). For the IT analysts the user is a user of tools; however, for the librarian, the user is the information user. The IT analyst frequently also sees the user in the role of a consumer. But, although they deal with different users users of information, digital information systems and tools who can converge when there is an interest in the informational supplies, the librarians and IT analysts measure the success of their actions by the success in the use of the systems, products of the library itself, in a system-oriented approach, from the point of view of user studies. In general, theoretical references are not indicated to help the activities of explicit mediation conducted by the professionals (in the reference services of libraries and in the user help system of computer information systems), tacit and practical references predominate instead. On the other hand, in activities related to computer information systems design, there is an actual incorporation of bibliographical references of software and/or usability engineering. Common research techniques are used to conduct user studies among those interviewed with a profile of requirement/systems analysts and librarians with experience in the digital systems design like interviews and domain analysis in the project of computer systems. Quantitative research techniques are predominant in the user studies formally conducted by the librarians. However, qualitative techniques observation, interview and software engineering and usability technical methods prototyping are used by IT analysts with a profile of interaction designers or usability experts.